Compound surfactant-based emulsion method for the preparation of high-porosity alumina microspheres. Issue 16 (15th August 2022) - Zhao, Jiansen; Han, Pengda; Li, Jiangtao; Hu, Xiaoxia; Guo, Anran; Yang, Shuo; Du, Haiyan
Abstract: Porous alumina microspheres have attracted significant attention owing to their high mechanical strength and excellent chemical and thermal stability. The emulsion method is considered as a simple and controllable method for the preparation of inorganic microspheres. However, preparing alumina microspheres with the emulsion method is challenging because the emulsification of the precursor is inhibited by the rapid hydrolysis of aluminum alkoxide. Herein, we report a new emulsion method for the preparation of high-porosity alumina microspheres using a combination of ionic and non-ionic surfactants; in this method, the compound surfactants act as a template agent to guide aluminum alkoxide to form a lamellar structure through self-assembly. The decomposition of the templating agent and transformation of the alumina crystal at a high temperature result in structural collapse and formation of lamellar pores. Compound surfactants increased the spheroidization rate of the emulsion from 47% to 63% after hydrolysis, whereas the particle size was decreased by almost half. Additionally, the morphology and porosity of the alumina microspheres were changed. With increasing anionic surfactant content, the porosity increased initially and then decreased. The porosity of the alumina microspheres reached a maximum value of 76% at the 1:1 mass ratio of the non-ionic to anionic surfactants. Heat treatment was found to change the size of lamellar pores, with the pore diameter reaching maximum value at 1300 °C. The compound surfactants also increased the compressive stress and specific surface area of the porous alumina microspheres.